Socio-Cultural Influences on Fashion Consumption Behaviour of University Students - Anyanwu, Elisha Chika; Chiana, Cyril Anamelech (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study aimed at investigating the social-cultural influences on fashion consumption behaviour among undergraduate university students basing on the theory of reasoned action (TRA). The population of the study was mainly the Management Science students from two universities from the South-East and South-South Zones of Nigeria. The sample size was 278 while valid response was 256. The survey was based on likert scale structured questionnaire, while the proposed model was tested with the SPSS version 21 Simple Regression Analysis (SRA). It was found that culture, opinion leadership, social class, family and ethnicity have significant influence on fashion consumption among undergraduate students. The study recommends amongst others that marketers in the fashion business should continuously scan their social-cultural environment and assess its influence on consumer’s behaviour both at the personal and societal level with a view to enhancing their capacity to recognize, resist as necessary, and make international decision that will both be beneficial to them and their customers.